Evaluation of type-2 diabetes mellitus patients for dyslipidemia in a tertiary care centre - Chokshi, Janak G.; Gandhi, Apal P.; Parmar, Ishvarlal M.; Damor, Dipen R. (International Journal of Advances in Medicine, 2020)
Background: Diabetes mellitus (DM) is a syndrome consisting of metabolic, vascular and neuropathic components that are interrelated. Diabetes mellitus is associated with a considerably increased risk of premature atherosclerosis, particularly coronary heart disease (CHD) and peripheral arterial disease. Dyslipidemia is a common feature of diabetes. There is an association between atherosclerotic cardiovascular disease and serum cholesterol and triglyceride levels in both type 1 and type 2 diabetes. Methods: The study was done on 50 adult diabetes mellitus (T2) patients from IPD of General Medicine wards at SMS Hospital, Ahmedabad, Gujarat. 50 healthy age and sex matched healthy volunteers were taken as control. They were evaluated for lipid profile i.e., Total Cholesterol (TC),Triglyceride (TG), Low-density lipoprotein (LDL), High density lipoprotein (HDL), Very low density lipoprotein (VLDL) and glycemic status i.e., Fasting blood glucose (FBS), Postprandial 2 hours blood glucose (PP2BS) & Glycosylated haemoglobin(HbA1C). Results: Diabetic cases had statistically highly significant (p<0.001) elevated levels of total Cholesterol, Triglycerides and VLDL as compared to controls. Serum TG, serum TC, LDL-C and VLDL-C had positive correlation with the postprandial plasma glucose, fasting plasma glucose and HbA1c. Conclusions: Significant correlations between HbA1c levels and lipid levels point towards the usefulness of HbA1c for screening high-risk diabetic patients. High TC, TG, LDL-C and HbA1c with normal or low HDL-C is seen in almost all diabetic patients either alone or in combinations.